Pengaruh Intellectual Capital dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Ayu Anjani; Vaya Juliana Dillak (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2019)
Maximizing firm value is one of the company's goals. The high value of the firm indicates that the firm is able to maintain business continuity and is able to improve the prosperity of shareholders. This study aims to determine the effect of intellectual capital (VACA, VAHU, STVA) and company size (Ln of Total Assets) on firm value (PBV). The research was conducted at the consumer goods manufacturing company listed on the Indonesia Stock Exchange in 2014-2017. The sampling technique used was purposive sampling and obtained 18 companies that 72 sample data were obtained. The method of data analysis in this study is multiple linear regression analysis using SPSS 23 software. The results of the study show that simultaneously value added capital employed (VACA), value added human capital (VAHU), structural capital value added (STVA) and company size (Ln of Total Asset) have a significant effect on firm value (PBV).